2008
DOI: 10.1007/s10661-008-0566-1
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic evaluation of different doses of inorganic lead (PbII) in Hoplias malabaricus

Abstract: Different genetic biomarkers have been used to evaluate the pollution effects of mutagenic agents such as metals and also a great variety of chemicals delivered on the environment by human activities. This way, the aim of the present report was to evaluate the effects of inorganic lead in fishes through the frequency of piscine micronuclei and nuclear morphological alterations in peripheral cells, chromosomal aberration frequency and comet assays in blood and kidney cells. Specimens of Hoplias malabaricus rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 35 publications
1
30
0
1
Order By: Relevance
“…Thus, when considering frequency per 1,000 cells, MNs were 0.08 ± 0.13 in Hoplias malabaricus (Ferraro et al , 2004), 0.1 ± 0.316 in Eigenmannia virescens (Bücker et al , 2006), 3.17 ± 0.48 in Carassius auratus (Çavas and Könen, 2007), and 2.4 ± 1.19 in Colossoma macropomum (present paper). Furthermore, in MN assaying undertaken by Ramsdorf et al (2009), using H. malabaricus, there were no MNs, only nuclear morphological alterations.…”
mentioning
confidence: 89%
“…Thus, when considering frequency per 1,000 cells, MNs were 0.08 ± 0.13 in Hoplias malabaricus (Ferraro et al , 2004), 0.1 ± 0.316 in Eigenmannia virescens (Bücker et al , 2006), 3.17 ± 0.48 in Carassius auratus (Çavas and Könen, 2007), and 2.4 ± 1.19 in Colossoma macropomum (present paper). Furthermore, in MN assaying undertaken by Ramsdorf et al (2009), using H. malabaricus, there were no MNs, only nuclear morphological alterations.…”
mentioning
confidence: 89%
“…Pb in muscle was also frequently linked to genotoxicity in the current study. Previous studies reported genotoxic effects on Hoplias malabaricus (Ramsdorf et al, 2009) and Prochilodus lineatus (Monteiro et al, 2011) in response to inorganic Pb (Pb II) exposure. This metal has also been associated with lethality in fish, as well as with decreased reproductive performance, growth inhibition, and changes in behavior under sub-lethal exposure (Burdena et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Variations in the damage to genetic material is expected in different tissues because of the differential background levels of DNA single-strand breaks in tissues with different amounts of excision repair, and also because of different metabolism levels and concentrations of antioxidants (Lee and Steinert, 2003;Ali et al, 2008). The higher responsiveness of blood tissue to contaminants was explained due to the greater lifespan of circulating erythrocytes in comparison to cells in kidney, liver, and gill tissues (Ramsdorf et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the natural environment, the trahira H. aff. malabaricus exhibits ambush feeding on fish species, thereby expending low levels of energy on predation (Ferreira, 2007;Ramsdorf et al, 2009;Petry et al, 2010). The small artificial environment in which this experiment was carried out favored prey detection by the juveniles, which did not spend much energy on feeding activity.…”
Section: Discussionmentioning
confidence: 99%